Implementation of the INTERGROWTH‐21st Project in Italy. (11th July 2013) - Giuliani, F; Bertino, E; Oberto, M; Di Nicola, P; Gilli, G; Knight, HE; Cheikh Ismail, L; ,
Abstract : Turin, Italy, was one of the two European sites for the INTERGROWTH‐21 st Project. The sample for the Newborn Cross‐Sectional Study (NCSS) was drawn from two obstetric hospitals that together account for 79% of the city's approximately 12 000 births per year. Women were recruited for the Fetal Growth Longitudinal Study (FGLS) from ten antenatal clinics serving the city's largest obstetric hospital, Azienda Ospedaliera OIRM—S. Anna. Special activities to encourage participation and raise awareness of the project in this population included obtaining an endorsement from the coordinator of the city's antenatal care service, and disseminating information about the project to women through posters and leaflets in antenatal clinics. One of the major challenges at this site was the low recruitment rate in the early phase of FGLS because of the high prevalence of smoking and of women >35 years old in the population. The addition of six extra recruiting clinics served to increase the pool of potentially eligible women who could be screened and led to a marked improvement in the recruitment rate.